Synthesis of Pyrethroids and Jasmonoids through Palladium-Catalyzed Cross-Coupling Reactions - Parpal, Florencia; Paullier, Ana Paula; Pandolfi, Enrique; Heguaburu, Viviana (Synthesis, 2022)
The synthesis of jasmone and related jasmonoids and pyrethroids is described. These compounds play a defensive role in plants and share a common cyclopentenone core with variations in the side chains. Jasmone, cinerone, allylrethrone, and derivatives were synthesized through π-allyl palladium cross-coupling of stannane derivatives. With selective hydrogenation, dihydrojasmone, and dihydrocinerone were also synthesized.
Keywords: allylrethrone; cinerone; cross-coupling; dihydrojasmone; jasmone